Efeito da intervenção fisioterapêutica na modulação autonômica da freqüência cardíaca de pacientes com infarto agudo do miocárdio: fase I da reabilitação cardiovascular - Santos, Michele Daniela Borges dos (Universidade Federal de São Carlos, 2006)
The purpose of the present study was to evaluate the effects of physiotherapeutic intervention on the autonomic control of heart rate through heart rate variability (HRV) indices at rest (supine and seated positions), during deep breath test (DBT), during an exercise protocol and during walking, in patients with acute myocardial infarction (AMI) submitted to phase I of cardiac rehabilitation. Second, evaluate the effects of an inspiratory muscle training (IMT) on the maximal inspiratory pressure (PImax) and on the magnitude of respiratory sinus arrhythmia (RSA). Initially, thirty five patients of both genders were studied in the 1st stage of the cardiovascular physiotherapy (CPT), however, only eighteen of them performed all six stages of treatment (mean = 56± 13 year). These patients, who were admitted to the Coronary Care Unit (CCU) (two days) and the ward (four days) of the Santa Casa de Misericórdia de São Carlos with noncomplicated AMI, were hemodynamically stable and used conventional medications. The 1st stage was initiated 22± 5 hours after the CCU admission and the progression to other 5 stages was done based in the daily clinical evolution of each patient. This stage included 10 minutes of rest (pre and post-exercise protocol), 4 minutes of deep breathing test and 5 minutes of exercise protocol (active-assisted low extremities exercises) in the supine position. Furthermore, the 6th stage included 10 minutes of rest in the supine position (pre and post-intervention), 4 minutes of deep breathing test, 5 minutes of rest in the seated position (pre and post-intervention), 5 minutes of active low extremities exercises in the orthostatic position and 15 minutes of walking. The instantaneous heart rate (HR) and the R-R interval (RRi) were acquired by a HR monitor (Polar S810) during all stage and the blood pressure (BP) was measured before and after each stage. Additionally, the PImax was measured (in the seated position) through a manuvacuometer at the pre and post-IMT, which was performed at the 2nd to 6th stages. The intensity of IMT was settled at 40% of PImax pressure load. The HRV was analyzed by time (RMSSD and RMSM indices) and frequency (Fast Fourier Transform) domain methods. The power spectral density was expressed as normalized units (nu) at low (LF) and high (HF) frequencies, and as the LF/HF. Results: The cumulative effect of physiotherapeutic intervention caused increase of AFnu (p<0.05) and decrease of LFnu (p<0.05) when they were evaluated at the rest pre-intervention in the supine position and during exercise protocol of 1st and 6th stages. Additionally, decreased LF/HF was also observed at rest pre-intervention in the supine position. However, no changes were observed for these indices when the 1st and 6th stages were compared to during the RSA, in the rest post-intervention (supine position) and in the rest pre and post-intervention (seated position), and the 4th and 6th stages were compared to during the walking. In the time domain, RMSM and RMSSD diminished at 1st to 6th stages for rest post-intervention in supine position. The IMT augmented the PImax in 46% (P<0.05), but increased PImax and the RSA magnitude did not correlate among them. Conclusion: The CPT realized in the phase I of the cardiac rehabilitation caused increase in the vagal activity and decrease the sympathetic activity during rest and exercises conditions, since the beta-blockade and IECA medications dosages were not altered. Additionally, the intensity used in the IMT was able to improve the PImax, but it did not influence on the RSA magnitude. Financial support: FAPESP (04/05788-6) and CNPq (478799/2003-9).
Effects of physiotherapy intervention on the autonomic control of heart rate in acute myocardial infarction patients: phase I of cardiac rehabilitation
Keywords: Fisioterapia; Sistema nervoso autônomo; Enfarte do miocárdio; variabilidade da freqüência cardíaca; Coração - doenças - pacientes - reabilitação; Heart rate variability; Autonomic nervous system; Acute Myocardial infarction; Cardiovascular physiotherapy; Phase I of cardiac rehabilitation; Respiratory sinus arrhythmia; Inspiratory muscle training; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL